Q. 73.8( 6 Votes )

# In each of the fo

Answer :

We have,

f(x) = 9x3-3x2+x-5 and g(x) = x= Therefore, by remainder theorem when f (x) is divided by g (x) = x - , the remainder is equal to f ( )

Now, f(x) = 9x3-3x2+x-5

f ( ) = 9 ( )3 – 3 ( )2 + – 5

= (9 * ) – (3 * ) + – 5

= - + – 5

= 2 – 5 = -3

Hence, the required remainder is -3.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Division of Polynomials46 mins  Quiz- Test what you Know Part 246 mins  Polynomials- Introduction45 mins  Identities Ke Master Bane47 mins  Quiz- Test what you Know64 mins  Conservation of Energy41 mins  Pair of Angles29 mins  Complete Basics of Class 9 Chemistry - I35 mins  Equations of Motion41 mins  Graphical Representation of Motion - II39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics